Assessing the brand meaning of an interdisciplinary engineering programme through a branding method. (22nd July 2011) - Elrod, Cassandra C.; Lough, Katie Grantham; Adams, Kevin
This paper presents the brand status of the Interdisciplinary Engineering (IDE) degree programme at Missouri University of Science and Technology (Missouri S&T), formerly the University of Missouri-Rolla (UMR). The IDE degree was founded in 2005 at UMR to meet the emerging need to provide considerable flexibility to students allowing them to construct programmes of study in areas of interest while maintaining a foundation in mechanics, thermal science, electrical networks and linear systems. This paper presents the brand status of the IDE BS degree among prospective and current students, academic faculty, and industry, and weighs it against the original implementation plan proposed in 2005 and provides the current perception of the degree programme at Missouri S&T.